The impact of ethnicity on stroke care access and patient outcomes: a New Zealand nationwide observational study - Stephanie G. Thompson; P. Alan Barber; John H. Gommans; Dominique A. Cadilhac; Alan Davis; John N. Fink; Matire Harwood; William Levack; Harry McNaughton; Valery L. Feigin; Virginia Abernethy; Jackie Girvan; et al. (Elsevier, 2022)
Summary: Background: Ethnic inequities in stroke care access have been reported internationally but the impact on outcomes remains unclear. In New Zealand, data on ethnic stroke inequities and resultant effects on outcomes are generally limited and conflicting. Methods: In a prospective, nationwide, multi-centre observational study, we recruited consecutive adult patients with confirmed stroke from 28 hospitals between 1 May and 31 October 2018. Patient outcomes: favourable functional outcomes (modified Rankin Scale 0-2); quality of life (EQ-5D-3L); stroke/vascular events; and death at three, six and 12 months. Process measures: access to reperfusion therapies, stroke-units, investigations, secondary prevention, rehabilitation. Multivariate regression analyses assessed associations between ethnicity and outcomes and process measures. Findings: The cohort comprised 2,379 patients (median age 78 (IQR 66-85); 51·2% male; 76·7% European, 11·5% Māori, 4·8% Pacific peoples, 4·8% Asian). Non-Europeans were younger, had more risk factors, had reduced access to acute stroke units (aOR=0·78, 95%CI, 0·60-0·97), and were less likely to receive a swallow screen within 24 hours of arrival (aOR=0·72, 0·53-0·99) or MRI imaging (OR=0·66, 0·52-0·85). Māori were less frequently prescribed anticoagulants (OR=0·68, 0·47-0·98). Pacific peoples received greater risk factor counselling. Fewer non-Europeans had a favourable mRS score at three (aOR=0·67, 0·47-0·96), six (aOR=0·63, 0·40-0·98) and 12 months (aOR=0·56, 0·36-0·88), and more Māori had died by 12 months (aOR=1·76, 1·07-2·89). Interpretation: Non-Europeans, especially Māori, had poorer access to key stroke interventions and experience poorer outcomes. Further optimisation of stroke care targeting high-priority populations are needed to achieve equity. Funding: New Zealand Health Research Council (HRC17/037).